2009
DOI: 10.1111/j.1744-7917.2009.00252.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of host (Boettcherisca peregrina) copper exposure on development, reproduction and vitellogenesis of the ectoparasitic wasp, Nasonia vitripennis

Abstract: Effects of copper (Cu) accumulation by the flesh fly Boettcherisca peregrina (R.-D.) (Diptera: Sarcophagidae) on the ectoparasitic wasp Nasonia vitripennis (Walker) (Hymenoptera: Pteromalidae) were investigated experimentally by exposing host larvae to contaminated diets with final Cu concentrations of 400 +g/g and 800 +g/g diet fresh weight (DFW), respectively. Results showed that Cu can be transferred along food chains to secondary consumers (parasitoids) in small amounts, resulting in negative effects on pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…HM contaminated prey or water sources have been revealed to lengthen development time [44][45][46][47][48]. For example, when feeding on hosts contaminated with copper (Cu), Nasonia vitripennis (Hymenoptera: Pteromalidae), exhibited lengthened developmental time and reduced emergence of adult parasitoids from the pupal stage [45]. The adult wasps also had a shortened adult life span and females exhibited reduced fecundity [45].…”
Section: Development Time and Body Sizementioning
confidence: 99%
See 1 more Smart Citation
“…HM contaminated prey or water sources have been revealed to lengthen development time [44][45][46][47][48]. For example, when feeding on hosts contaminated with copper (Cu), Nasonia vitripennis (Hymenoptera: Pteromalidae), exhibited lengthened developmental time and reduced emergence of adult parasitoids from the pupal stage [45]. The adult wasps also had a shortened adult life span and females exhibited reduced fecundity [45].…”
Section: Development Time and Body Sizementioning
confidence: 99%
“…For example, when feeding on hosts contaminated with copper (Cu), Nasonia vitripennis (Hymenoptera: Pteromalidae), exhibited lengthened developmental time and reduced emergence of adult parasitoids from the pupal stage [45]. The adult wasps also had a shortened adult life span and females exhibited reduced fecundity [45]. Interestingly, exposure to HMs results in reduced body mass in some predators [48] and greater body mass in others [49].…”
Section: Development Time and Body Sizementioning
confidence: 99%
“…Host quality is an important feature of the prey of parasitoids and predators, and the elemental composition of hosts can affect quality (Ye et al, 2009). For example, Vickerman and Trumble (2003) showed that consumption of high-Se herbivore prey negatively affected the predacious bug Podisus maculiventris (Heteroptera: Pentatomidae).…”
Section: '' Ecological Consequences Of High-ni Insects: Effects On Prmentioning
confidence: 99%
“…'' Because hyperaccumulation in plants has been suggested to constitute an elemental defense against herbivores (Martens & Boyd, 1994;Boyd, 2007b), it is natural to ask if elemental defense extends to organisms occupying other trophic levels (Boyd, 1998a). Host quality is an important feature of the prey of parasitoids and predators, and the elemental composition of hosts can affect quality (Ye et al, 2009). For example, Vickerman and Trumble (2003) showed that consumption of high-Se herbivore prey negatively affected the predacious bug Podisus maculiventris (Heteroptera: Pentatomidae).…”
Section: '' Ecological Consequences Of High-ni Insects: Effects On Prmentioning
confidence: 99%
“…The contribution of Ye et al (2009) shows transmission of Cu from insect host to parasitoid wasp and presents evidence that the negative impact of host Cu on the wasp stems from decreased host quality rather than effects of Cu stress per se. My contributions stem from my interest in Ni hyperaccumulator plants (which as their name implies contain unusually large concentrations of Ni) and the insects that feed on them.…”
mentioning
confidence: 99%